[Translated article] Concurrent upper limb and hip fracture in the elderly: Experience at our centre - L. del Baño-Barragán; Á. Martínez-García; D. Garríguez-Pérez; J. Mora-Fernández; J. García-Coiradas; J.A. Valle-Cruz; F. Marco (Revista Española de Cirugía Ortopédica y Traumatología)
Introduction: The incidence of hip fracture in the elderly is on the rise, occasionally accompanied by concurrent upper limb fractures. Our investigation aims to determine whether these patients experience poorer functional outcomes, prolonged hospitalisation, or higher mortality rates when compared to those with isolated hip fracture. Material and methods: We retrospectively reviewed 1088 elderly patients admitted to our centre with hip fracture between January 2017 and March 2020. We recorded the presence of concomitant fractures and their treatment. We analysed the duration of hospital stay, in-hospital mortality and function. Results: We identified 63 patients with concomitant upper limb fracture (5.6%). Among them, 93.7% were women, and the average age was 86.4 years. 80.9% of the upper limb fractures were distal radius or proximal humerus. Patients with concomitant fracture had increased length of stay (mean, 19.6 vs. 12.8, p = 0.002), decreased proportion of patients returning to their own home at discharge (23.6% vs. 26.3%, p = 0.042) and increased in-hospital mortality rate (9.5% vs. 5.9%, p = 0.003). Conclusions: Patients with concomitant upper limb fracture require a longer length of stay and exhibit an elevated in-hospital mortality rate. Furthermore, this condition is associated with a reduced short-term functional recovery, thereby decreasing the chances of the patient returning home upon hospital discharge. Resumen: Introducción: La incidencia de las fracturas de cadera en los ancianos está en aumento, a veces acompañada de fracturas concomitantes en miembros superiores. Nuestro estudio tiene como objetivo determinar si estos pacientes experimentan peores resultados funcionales, una tasa de hospitalización más prolongada o tasas de mortalidad más elevadas en comparación con aquellos con fractura de cadera aislada. Material y métodos: Realizamos una revisión retrospectiva de 1.088 pacientes ancianos ingresados en nuestro centro con fractura de cadera, entre enero de 2017 y marzo de 2020. Registramos la presencia de fracturas concomitantes y su tratamiento. Analizamos la duración de la estancia hospitalaria, la mortalidad intrahospitalaria y la funcionalidad de los pacientes al alta. Resultados: Identificamos 63 pacientes con fractura concomitante de miembro superior (FCMS) (5,6%); de ellos, el 93,7% fueron mujeres y la media de edad fue de 86,4 años. El 80,9% de las FCMS fueron fracturas de radio distal o húmero proximal. Los pacientes con FCMS presentaron una mayor estancia hospitalaria (media, 19,6 vs. 12,8, p = 0,002), una menor proporción de pacientes que se fueron de alta a su domicilio (23,6% vs. 26,3%, p = 0,042) y una mayor tasa de mortalidad intrahospitalaria (9,5% vs. 5,9%, p = 0,003). Conclusión: Los pacientes con FCMS requieren una estancia hospitalaria más prolongada y presentan una tasa de mortalidad intrahospitalaria elevada. Además, esta condición se asocia con una reducida recuperación funcional a corto plazo, disminuyendo la probabilidad de que el paciente pueda regresar a su domicilio al alta hospitalaria.